Coupled KIPP-EDGE2D modelling of parallel transport in the SOL and divertor of inter-ELM JET high radiative H-mode plasma. (1st September 2022) - Chankin, A V; Corrigan, G; Coster, D P; ,
Abstract: The Kinetic Code for Plasma Periphery (KIPP) models parallel (along magnetic field lines) propagation of charged particles in the scrape-off layer (SOL) and divertor of tokamaks. An iterative coupling between KIPP and a 2D edge fluid code EDGE2D, which in turn is coupled to the Monte-Carlo solver EIRENE for neutrals, was used to achieve a converged KIPP-EDGE2D-EIRENE solution. The original EDGE2D-EIRENE solution simulated SOL and divertor of JET high radiative inter-edge localized mode H-mode plasma conditions with strong nitrogen injection, leading to partial detachment at divertor targets. This work is a continuation of earlier studies of modelling kinetic electrons (Chankin et al 2018 Plasma Phys. Control. Fusion 60 115011) and ions (Chankin et al 2020 Plasma Phys. Control. Fusion 62 105022) with KIPP. For numerical reasons caused by large cell-to-cell plasma parameter variations near entrances to divertors, multipliers for parallel electron and ion conductive power fluxes (KIPP/EDGE2D ratios) which are passed onto EDGE2D, could only be used in the main SOL, outside divertors. There, the heat flux limiting effect led to an increase in maximum plasma temperatures in the main SOL and a decrease in power fluxes to divertor targets. Results of the coupling studies are consistent with earlier studies, suggesting that under investigated JET plasma conditions kinetic effects of charged particle parallel propagation do not drastically change target power deposition at divertor targets calculated by EDGE2D-EIRENE along.